1992
DOI: 10.1159/000468794
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oxidation Activity and Biological Role of Human Cytosolic Aldehyde Dehydrogenase

Abstract: The major cytosolic aldehyde dehydrogenase isozyme (ALDH1) exhibits strong activity for oxidation of retinal to retinoic acid, while the major mitochondrial ALDH2 and the stomach cytosolic ALDH3 have no such activity. The K(m) of ALDH1 for retinal is about 0.06 μmol/l at pH 7.5, and the catalytic efficiency (Vmax/Km) for retinal is about 600 times higher than that for acetaldehyde. Thus, ALDH1 can efficiently produce retinoic acid from retinal in tissues with low retinal concentrations (<0.1 μmol/l). The gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
94
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 9 publications
7
94
0
Order By: Relevance
“…This analysis supports the specific branching orders for the major groups, which are ((ALDH6, ALDH1) and (ALDH5, ALDH2)), ALDH9) as shown in the tree by Yoshida et al (62). Proteins with catalytic activity converting retinal to RA are indicated by asterisks (20,22,23,38,39,45,(52)(53)(54)(55)57 …”
Section: ϫ4mentioning
confidence: 99%
“…This analysis supports the specific branching orders for the major groups, which are ((ALDH6, ALDH1) and (ALDH5, ALDH2)), ALDH9) as shown in the tree by Yoshida et al (62). Proteins with catalytic activity converting retinal to RA are indicated by asterisks (20,22,23,38,39,45,(52)(53)(54)(55)57 …”
Section: ϫ4mentioning
confidence: 99%
“…Although previous studies have demonstrated that CD133 and CD44 are the most robust markers for lung CSCs, their co-expression has not yet been evaluated in lung cancer. CSCs can also be identified or isolated using the activity of aldehyde dehydrogenase 1 (ALDH1), which is involved in the detoxification of intracellular aldehydes, oxidation of retinol to retinoic acid, and early stem cell differentiation [16]. Some recent studies demonstrated that ALDH1 + lung cancer cells display in vitro and in vivo CSC features, so ALDH1is identified as a lung cancer stem cell-associated marker [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SEC topology influences ALDH1/2 substrate preference. For example, although retinaldehyde is a good substrate for vertebrate ALDH1s and acetaldehyde is a natural substrate of ALDH2s, ALDH2s cannot process retinaldehyde and ALDH1s process acetaldehyde only extremely inefficiently (16,(17)(18)(19)(20)(21)(22).To understand the evolutionary origins of the substrate preferences of ALDH1 and ALDH2 enzymes, as well as to illuminate how signaling and protective functions are connected to these different enzyme activities, we used an integrated approach that combined genomic, phylogenetic, and structural analyses. The resulting comprehensive data set was complemented with information on developmental gene expression of ALDH1/2s in the cephalochordate amphioxus (Branchiostoma floridae) and the ascidian tunicate Ciona intestinalis.…”
mentioning
confidence: 99%
“…Thus, SEC topology influences ALDH1/2 substrate preference. For example, although retinaldehyde is a good substrate for vertebrate ALDH1s and acetaldehyde is a natural substrate of ALDH2s, ALDH2s cannot process retinaldehyde and ALDH1s process acetaldehyde only extremely inefficiently (16,(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
See 1 more Smart Citation